Cushioning properties of 3D printed polymers - Wong, Zi Hao (2016)
Additive Manufacturing (AM), also known as 3D printing, is a process where an object is created by adding material layer-by-layer under computer control. With computer-aided design (CAD) software, users are able to create simple and intricate objects quickly and economically without the need for tooling. 3D printing has been adopted in various industries, changing the way they operate. In this study, static compression tests at low and high compression rates were conducted on 3D printed polymers by ProJet MJP 5500X from 3D Systems to determine its cushioning properties. Combinations of rubber-like (VisiJet CF-BK) and plastic-like (CR-CL) materials were printed and tested. This study will employ two parameters, efficiency of energy absorption and ideality of energy absorption, to determine the cushioning properties of the 3D printed polymers at high and low strain rates. It was found that VisiJet CF-BK and RWT-FBK 500 (a multi-material composite) displayed optimal cushioning properties at low and high stresses respectively. The results obtained at low and high compression rates of VisiJet CF-BK and RWT-FBK 500 showed similar trends.